Online learning: the brave new world of massive open online courses and the role of the health librarian. (March 2016) - Spring, Hannah
Abstract: In a wired, virtual and information rich society, MOOCs (Massive Open Online Courses) are leading us into a brave new world in which their key role is to support lifelong networked learning. This feature looks at the broad role of MOOCs and considers them within the context of health, and health librarianship. In particular, it provides examples of where health librarians have developed MOOCs and what opportunities there are in the future for health librarians to collaborate in the development and delivery of health MOOCs. H.S.